Venous Adventitial Cystic Disease: A Review of 45 Cases Treated Since 1963. (3rd November 2016) - Bascone, Corey; Iqbal, Mazen; Narh-Martey, Patrick; Szuchmacher, Mauricio; Cicchillo, Michael; Krishnasastry, Kambhampaty V.
Abstract : Purpose . To review and identify the most accurate ways of diagnosing and treating adventitial cystic disease (ACD) of the venous system. Methods . Cases of ACD were collected through three popular medical databases, including PubMed, Cochrane, OVID, and MEDLINE. After reviewing the literature, the sites of occurrence of 323 cases of adventitial cystic disease were documented, and all cases of arterial ACD were excluded. The clinical features, treatment, and subsequent course of 45 cases of venous ACD are included in this paper. Results . After reviewing all 45 cases of venous ACD, we have confirmed that the most common vessel affected is the common femoral vein, which reproduces the most common symptom of venous ACD: asymmetric lower extremity swelling worsening over time. Conclusion . Venous ACD most commonly affects the common femoral vein. When unilateral leg swelling occurs with or without a noticeable mass, ACD should be considered. It is best confirmed with CT venography and the treatment of choice is transluminal cyst evacuation and excision.